Cover Feature: Recent Developments in the Meyer‐Schuster Rearrangement (Eur. J. Org. Chem. 4/2021). Issue 4 (19th January 2021) - Justaud, Frédéric; Hachem, Ali; Grée, René
Abstract : The Cover Feature shows the remarkable progress of the venerable MSR reaction during the last decade. Like superb fireworks, sparkling results were obtained in many directions as presented in this review article. It includes the discovery of novel and very efficient catalysts, or multicatalytic systems, and the use of MSR for innovative cascade processes to prepare many carbo‐ and heterocycles. Moreover, elegant applications of MSR have been reported for the preparation of complex natural products. Finally, the first examples of the aza‐variant of MSR were published also in the recent years. More information can be found in the Review by René Grée et al.